The effect of spiritual group therapy on death anxiety in the elderly - Soudabeh Aloustani; Leila Mamashli (Tehran University of Medical Sciences, 2020)
Background & Aim: The experience of approaching death is one of the undeniable facts of aging that can cause fear and anxiety in the elderly. Given that spirituality as a solid base can be a powerful factor in controlling tense situations, this study was conducted to examine the effect of spiritual group therapy on death anxiety in the elderly. Methods & Materials: This quasi-experimental study was conducted on 50 elderly people attending the elderly daily center in Aliabad Katoul (Golestan Province) in 2018. Sampling was done using the convenience method and participants were randomly assigned into either experimental- or control group. The experimental group received spiritual group therapy in 8 sessions within eight weeks. The data were collected using a demographic characteristics questionnaire and the Templer death anxiety scale. Using the SPSS software version 16, data were analyzed through independent t-test, paired t-test and covariance test at a significance level of less than 0.05. Results: The rate of death anxiety before the intervention in the experimental- and control group were 7.36±3.67 and 7.32±1.65 respectively, which did not show a statistically significant difference (P=0.961). After the intervention, the average score of death anxiety for the experimental group was 5.24±3.28 and for the control group was 7.84±1.92 which showed a statistically significant difference (P<0.001). Conclusion: According to the results, it is recommended to provide the necessary conditions to the elderly to participate in spiritual activities, which can be effective in improving the psychological state of the elderly. Clinical trial registry: IRCT20181207041877N1